Common Cause Failure Analysis for Wireless Sensor Networks - Ivanovitch Silva (2013)
Simultaneous failures of multiple devices make thedominant contribution to the unreliability of wireless sensornetworks. They can hamper communications over long periods oftime and consequently disturb, or even disable, the managementalgorithms of the network. In this preliminary work, we considertwo types of common cause failures: hardware, and the temporary disruption of links. We propose an evaluation methodologybased on the fault tree formalism for analyzing the reliabilityand availability of any wireless sensor network when commoncause failures are considered.